Application of the concept of reflection in majejahitan activity by Bali Mulia society - Jero Budi Darmayasa; Wahyudin Wahyudin; Tatang Mulyana (Ethnomathematics Journal, 2020)
This research is qualitative research with case study method. The focus of this research is to explore the value of ethnomathematics in the culture of the Bali Mula society in the Kintamani sub-district, Bali Province. The research starts from the exploration phase of ethnomathematics, mapping ethnomathematics with school mathematics, explores aspects of pedagogy in the preservation of ethnomathematics and concludes on how ethnomathematics is applied to mathematics learning in schools. Data collection was carried out through observation of Mejejahitan activities carried out by Bali Mula women. Data from observations are then linked to the results of documentation analysis and strengthened by the results of interviews. The triangulation method is carried out to check the validity of the research data. Based on the results of data analysis there is a relationship between the activities of Mejejahitan with school mathematics. The mathematical concepts contained in the Majejahitan activity that is reflecting (reflecting) and predicting or predicting patterns. Because there is a relationship between Majejahitan activities with school mathematics, it can be said that there are ethnomathematics values in the culture of the Bali Mula society in Kintamani District, Bali Province.